Antiseptic Activity of Ethnomedicinal Xuebijing Revealed by the Metabolomics Analysis Using UHPLC-Q-Orbitrap HRMS - Zuo, Lihua; Zhou, Lin; Xu, Tanye; Li, Zhuolun; Liu, Liwei; Shi, Yingying; Kang, Jian; Gao, Guanmin; Du, Shuzhang; Sun, Zhi; Zhang, Xiaojian (Frontiers in Pharmacology, 2018)
Xuebijing (XBJ) injection is an ethnomedicinal formula that has been widely used in the therapy of sepsis in China. However, the underlying theraputic mechanisms remain uninvestigated. In this research, a metabolomic method based on UHPLC-Q-Orbitrap HRMS was applied to make a holistic evaluation of XBJ on septic rats which were induced by the classical cecal ligation and puncture (CLP) operation. The plasma metabolic changes were profiled and evaluated by multivariate analytical (MVA) methods. In the results, a total of 41 differential metabolites were identified between CLP-operated group and sham-operated group, which were mainly involved in amino acid metabolism and lipid metabolism. After pathway analysis, it was finally discovered that the majority of the influenced metabolic pathways caused by sepsis mainly involved in energy metabolism, oxidative stress and inflammation metabolism. When intervened by XBJ injection, 32 of the 41 disordered metabolites had been adjusted in reverse, which suggested that XBJ could mediate the abnormal metabolic pathways synergistically. In conclusion, the present study systematically investigated the efficacy and its underlying therapeutic mechanisms of XBJ on sepsis, while offering a new insight for the subsequent relevant exploration of other Chinese medicine at the same time.